Combinations of wet corn gluten feed and steam flaked corn in finishing cattle diets - J.J. Sindt; Sean P. Montgomery; T.B. Farran; H.J. LaBrune; R.D. Hunter; James J. Higgins; R.T. Ethington; R.U. Lindquist; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
A 152-day experiment was conducted using 615 crossbred steers to evaluate cattle performance when steam-flaked corn in finishing diets was replaced partially with wet corn gluten feed (CGF). Finishing diets contained no wet CGF (0CGF) or 30 and 60% CGF on a dry matter basis (30CGF and 60CGF). Ruminal and fecal pH increased linearly (P<.01) as the proportion of wet corn gluten feed increased. Cattle fed 60CGF gained less than those fed 30CGF (P<.01) and were less efficient than cattle fed 0CGF or 30CGF (P<.05). Dressing percentage was lower (P<.03) for cattle fed 60CGF compared to cattle fed 30CGF. Incidence of liver abscesses increased linearly (P<.01) as the level of CGF increased. Replacing steamflaked corn with wet CGF at 30% of the diet did not alter performance.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Wet corn gluten feed; Steam flaked corn; Finishing cattle